Control of natural convection heat transfer in ferrofluid filled trapezoidal cavities with a magnetic dipole source - Selimefendigil, Fatih; Öztop, Hakan Fehmi; Al-Salem, Khaled S. (Inderscience Enterprises Ltd, 2016)
In this study, a numerical study of natural convection ferrofluid filled trapezoidal enclosure was performed under the influence of a magnetic dipole source. The left inclined wall of the cavity is heated and the right inclined wall is kept at constant temperature lower than that of the heater. Other horizontal walls of the trapezoidal enclosure are assumed to be adiabatic. The governing equations are solved with finite element method. The influence of the Rayleigh number, inclination angle of the side walls, strength of the magnetic dipole, horizontal and vertical location of the magnetic dipole on fluid flow and heat transfer are numerically investigated. It is observed that increasing values of Rayleigh number and inclination angles enhance the heat transfer. The external magnetic field parameters (strength and location) can be used to control the heat transfer and fluid flow inside the trapezoidal cavity.
Keywords: magnetic dipole; natural convection; ferrofluid; finite element method